Constructing a conceptual framework of the smart apparel design using KJ methods for the disabled elderly - Juliza Jamian (Universiti Pendidikan Sultan Idris, 2018)
Constructing a conceptual framework of the smart apparel design using KJ methods for the disabled elderly by Juliza Jamian